Michael M. Bell, City of the Good: Nature, Religion, and the Ancient Search for What Is Right - Powell, Russell C. (Journal for the Study of Religion, Nature and Culture, 2021)
Michael M. Bell, City of the Good: Nature, Religion, and the Ancient Search for What Is Right (Princeton, NJ: Princeton University Press, 2018), 340 pp., 35 (hbk), ISBN: 9781400887934.